Clonal selection drives protective memory B cell responses in controlled human malaria infection - Murugan, Rajagopal; Höfer, Thomas; Wardemann, Hedda (Science immunology, 2018)
Memories of exposure - Protective memory B cell responses are shaped through multiple mechanisms, including clonal selection of naïve B cells and affinity maturation. Memory B cell responses are considered critical to the development of a successful malaria vaccine, and Murugan et al. characterize memory B cell responses to the Plasmodium falciparum circumsporozoite (PfCSP) protein in human volunteers immunized with sporozoites. They observed that repeated immunization induced potent responses to the immunodominant PfCSP NANP repeat by the clonal selection of naïve and preexisting memory B cell precursors and was less influenced by affinity maturation. Computational modeling indicated that these responses are shaped by the complexity of the antigen, and these findings provide a new perspective on protective B cell responses. - Affinity maturation, the clonal selection and expansion of antigen-activated B cells expressing somatically mutated antibody variants that develop during T cell-dependent germinal center reactions, is considered pivotal for efficient development of protective B cell memory responses to infection and vaccination. Repeated antigen exposure promotes affinity maturation but each time also recruits antigen-reactive naïve B cells into the response. Here, we determined the relative impact of affinity maturation versus antigen-mediated clonal selection of naïve B cells to mount potent B cell memory responses in humans after repeated exposure to a complex pathogen, the malaria parasite Plasmodium falciparum (Pf). Using single-cell immunoglobulin (Ig) gene sequencing and production of recombinant monoclonal antibodies, we analyzed the origin, development, and quality of memory B cell responses to Pf circumsporozoite protein (PfCSP), the major sporozoite surface protein. We show that after repeated immunization of Pf-naïve volunteers with infectious Pf sporozoites (PfSPZ Challenge) under chloroquine prophylaxis (PfSPZ-CVac), the clonal selection of potent germline and memory B cell precursors against the central PfCSP NANP repeat outpaces affinity maturation because the majority of Ig gene mutations are affinity-neutral. Mathematical modeling explains how the efficiency of affinity maturation decreases strongly with antigen complexity. Thus, in the absence of long-term exposure, the frequency of antigen-reactive precursors and likelihood of their activation rather than affinity maturation will determine the quality of anti-PfCSP memory B cell responses. These findings have wide implications for the design of vaccination strategies to induce potent B cell memory responses against PfCSP and presumably other structurally complex antigens. - The clonal selection of potent germline antibodies outpaces affinity maturation in human anti-PfCSP memory B cell responses. - The clonal selection of potent germline antibodies outpaces affinity maturation in human anti-PfCSP memory B cell responses.